Phosphate ‘sensing’ by human bone - Ito, Nobuaki; Kogawa, Masakagi; Wijenayaka, Asiri; Welldon, Katie J; Khalid, Kamarul Ariffin; Ormsby, Renee T; Atkins, Gerald J; Findlay, David M (Springer, 2011)
Aim: Osteocytes and osteoblasts produce the humoral factor, FGF23, which maintains serum levels of phosphate and 1, 25 dihydroxy vitamin D within the physiological range. This implies the ability to sense the levels of phosphate in blood and interstitial fluid, however there is no phosphate sensing mechanism has been identified in humans. In this study we investigated the ability of bone tissue to sense phosphate.